2016
DOI: 10.1515/afe-2016-0003
|View full text |Cite
|
Sign up to set email alerts
|

Low Cycle Mechanical and Fatigue Properties of AlZnMgCu Alloy

Abstract: The article presents the analysis of properties of the high-strength AlZnMgCu (abbr AlZn) aluminium alloy and estimates possibilities of its application for responsible structures with reduced weight as an alternative to iron alloy castings. The aim of the conducted studies was to develop and select the best heat treatment regime for a 7xx casting alloy based on high-strength materials for plastic working from the 7xxx series. For analysis, wrought AlZnMgCu alloy (7075) was selected. Its potential of the estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Pysz et al also found that the liquidus and solidus temperatures of 7075 Al alloy were 637.0 °C and 475.5 °C, respectively. The initial solidification temperature and peak temperatures of solidification were 632.8 °C and 625.1 °C [ 25 ]. The gap between the liquidus and solidus temperatures was 161.5 °C, and the nucleation undercooling of 7075 Al alloy was 4.2 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Pysz et al also found that the liquidus and solidus temperatures of 7075 Al alloy were 637.0 °C and 475.5 °C, respectively. The initial solidification temperature and peak temperatures of solidification were 632.8 °C and 625.1 °C [ 25 ]. The gap between the liquidus and solidus temperatures was 161.5 °C, and the nucleation undercooling of 7075 Al alloy was 4.2 °C.…”
Section: Resultsmentioning
confidence: 99%
“…This method description oriented towards problems concerning foundry alloys and their theoretical bases is presented in [13]. An example of this method of application in analyzing the casting of an automotive vehicle suspension (a so-called "rocker" made of an AlZnMgCu alloy) that allowed us to determine Parameters b and c resulting from the Manson-Coffin-Morrow dependence can be found in [14]:…”
Section: Modified Low-cycle Fatigue Testmentioning
confidence: 99%
“…[1,2,3,4,5,6] The 7xxx series as alloys used in the plastic forming are characterized by high strengths of over 500 MPa and good plasticity up to 20%. [7] The lack of metal forming (forging, rolling), eliminates one of the strengthening mechanisms which is squeeze hardening.…”
Section: Introductionmentioning
confidence: 99%